Information System-Based Curriculum Management in Vocational High Schools - Putri Ribcha Azzahra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Information system-based curriculum management is a strategic approach to improving curriculum quality in the digital era. Through the use of information systems, the curriculum can be planned, organized, implemented, and evaluated more efficiently, structured, and on-target. This study aims to determine how information system-based curriculum management is implemented at SMKN Cikalong, focusing on the process of curriculum planning, organization, implementation, and evaluation supported by information technology. The research method uses a qualitative approach with data collection techniques through interviews, observation, and documentation of teachers and students. The results show that the application of information systems in curriculum management can help schools design a curriculum that is more structured, efficient, and easily accessible to all school members. However, its implementation still faces obstacles, such as dependence on the internet network and a lack of training for educators. Therefore, optimizing the use of information systems in curriculum management is essential to ensure the learning process is increasingly relevant to developments in educational technology and to improve student quality and competitiveness in the digital age.